Implicit and explicit evaluations of foods: The natural and transformed dimension. (April 2019) - Coricelli, Carol; Foroni, Francesco; Osimo, Sofia Adelaide; Rumiati, Raffaella Ida
Highlights: Implicit and explicit evaluations of natural but not transformed foods appeared to be congruent. A bias in favor of natural foods rated as healthier has been found. Evaluations of transformed foods appeared to be dissociated in both unrestrained and restrained eaters. Hunger was found to modulate participants' explicit evaluations of food stimuli. Abstract: In Western societies, choosing what to eat can be a demanding task due to the excessive availability of food. To make our feeding decisions more complex, our explicit and implicit evaluations of foods may differ as they are multi-attribute stimuli. Previous research has focused on investigating implicit and explicit evaluations towards high and low energy dense foods, the main finding being that participants' hunger level and dietary habits (restrained eating) modulate such evaluations. In the present study, we investigated whether normal-weight healthy individuals assigned different values to natural and transformed foods depending on implicit (assessed with the Implicit Association Test) or explicit measures (assessed with explicit ratings), and whether participants' hunger level or dietary habits modulated the responses at both levels. Our results showed that while for natural foods implicit and explicit measures ( healthiness ) seemed to converge, dietary habits or hunger level did not affect such evaluations. For transformed foods, a dissociation between implicit and explicit measures ( healthiness ) seemed to emerge, along with a strong modulation of dietary habits and hunger level on the evaluations of such foods. Thus, these findings reveal how the type of food can modulate evaluations at both the implicit and explicit level and highlight a critical role of long-term health consequences and eating patterns in food evaluations.